The Present Status of the Agriculture Sector Towards Sustainable Development in Sri Lanka: A Review of Existing Policies and Suggestions for Improvements - S.D. Dilini Rathnachandra (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Agriculture plays a significant role in the national economy, helping to ensure food security and achieve sustainable development in Sri Lanka. This paper presents a review of the present situation of the agriculture sector and suggestions for the improvements needed to achieve sustainable development in Sri Lanka. As per the findings of the study, Sri Lanka had conventional agriculture practices a few decades ago, and agricultural policymakers were introduced to organic agriculture for commercial farming systems a few years ago. In particular, the application of organic agriculture practices has gradually reduced in commercial farming systems recently. This is because certain issues are still prominent in the agriculture sector: yield losses, lower ability to share the latest information and experiences of organic agriculture, lower responsiveness of hybrid seeds in organic farming, unavailability of properly directed organic agricultural regulations and national standards, post-harvest losses during long distance transportation, limited research and development, higher prices of organic products, higher input costs, higher susceptibility to pests and diseases, and a shortage of organic inputs, etc. As a result, the majority of agricultural authorities have introduced GAP farming practices for farmers. GAP is important to address the issues of food safety, trade, and sustainability. In addition to that, it also helps to reduce the unregulated use of agrochemicals, and avoid adverse climate change impacts or any negative externality that threatens the overall agriculture production, people's health, and the environment, thereby challenging the sustainability of the sector. Thus, pick-up orders at stations, usage of proper storage facilities to avoid post-harvest losses during long-distance transportation, formulating and implementing regulations for the development of the export market of GAP products, organising extension programs and training to disseminate the latest information to enhance farmers' adoption to GAP farming, encouraging field experts to gain international training opportunities, introducing proper control mechanisms to protect the local market, conducting research and development activities, and enhancing links between GAP farmers and other supply chain components to maintain a strong certification system for their products may lead to achieving sustainable agriculture development in Sri Lanka.